Whole-body amino acid pattern of juvenile, preadult, and adult pacu, Piaractus mesopotamicus, with an estimation of its dietary essential amino acid requirements - Khan, Kifayat U. [UNESP]; Mansano, Cleber F.M.; Nascimento, Thiago M.T. [UNESP]; Boaratti, André Z. [UNESP]; Rodrigues, Andressa T. [UNESP]; Queiroz, Daniel M.A. [UNESP]; Romaneli, Rafael S. [UNESP]; Sakomura, Nilva K. [UNESP]; Fernandes, João B.K. [UNESP] (Wiley, 2019)
In the present study, juvenile (live body weight, 54.3 ± 8.2 g), preadult (live body weight, 822.5 ± 33.9 g), and adult (live body weight, 1,562.8 ± 41.8 g) pacu, Piaractus mesopotamicus, were used to estimate their dietary essential amino acid (EAA) requirements using the whole-body amino acid (AA) pattern. The results showed that whole-body moisture, crude protein, total lipid, and ash contents expressed on a wet weight basis (%) were significantly different among the studied growth phases. No significant differences were observed in the dietary EAA requirements estimated for the three growth phases of pacu. These dietary EAA requirements were found to be different than those previously estimated for the same fish through its muscle AA pattern. Based on whole-body EAA to total EAA ratios {A/E ratios; [(each EAA/total EAA) × 1,000]}, EAA requirements were estimated to be histidine (0.42%), arginine (1.36%), threonine (0.82%), valine (0.90%), methionine (0.45%), isoleucine (0.83%), leucine (1.29%), phenylalanine (0.74%), lysine (1.64%), and tryptophan (0.14%) for pacu. These estimated requirements may serve as a reference line in the formulation of practical and experimental diets until dose–response-based optimum EAA requirements are available for pacu.
Keywords: A/E ratios; amino acid research; balanced diets; fish nutrition; ideal protein concept; pacu; whole-body amino acid pattern